The open container essentials video collection. (O'Reilly Media, 2016)
"The advent of open source containers has led to an explosion of innovation in the infrastructure space. This video collection includes detailed instruction on how to get the most out of the avalanche of products shaping the space today from Docker container workflows to Kubernetes management and OpenShift packaging and maintenance options."--Resource description page.